The Adaptation of the AAOIFI Shariah Standard Sharikah (Musharaka) and Modern Corporations in the Islamic Finance Industry of Pakistan - Umar Farooq; Muhammad Bilal Zafar (Universiti Sains Islam Malaysia, 2025)
The Journal of Muamalat and Islamic Finance Research, Volume 22 Issue 1 Page (167–181)